Community Empowerment Through Processing Waste into Fashion Products uses Heat Techniques Press to Increase Community Income in Senggigi Village, West Lombok District - Dakwah, Muhammad Mujahid; Roodhi, Mohammad Najib; Suprayetno, Djoko; Kusmayadi, Iwan; Abdurrahman, Abdurrahman; Muhtarom, Zamroni Alpian; Girsang, Zefanya Andryan; Apriadi, Apriadi; Denik Tirtaningrum, I Dewa Ayu (Institut Teknologi Nasional, Bandung, 2025)
The aim of this service activity is to empower the community by processing waste into fashion products using heat press techniques to increase community income in Senggigi Village, West Lombok Regency. The problem faced by partners is related to the large amount of plastic waste which, if burned, can produce dangerous compounds, apart from that, plastic waste can also damage the sustainability and beauty of the Senggigi tourism area. The method used to overcome this problem is in the form of community service activities which will be carried out to process waste into Fashion products using the Heat Press Technique, which is a new breakthrough in handling waste which can also increase income for the local community. As a result of partner activities, they have the ability to overcome the problem of increasing waste volume by managing waste into fashion products using heat press techniques.